2019
DOI: 10.1186/s12885-019-5695-0
|View full text |Cite
|
Sign up to set email alerts
|

Objective evaluation of clinical outcomes of laparoscopy-assisted pylorus-preserving gastrectomy for middle-third early gastric cancer

Abstract: Background Laparoscopic-assisted pylorus-preserving gastrectomy (LAPPG) is a minimally invasive function-preserving surgery for early gastric cancer. This study was designed to investigate the clinical outcomes between LAPPG and laparoscopy-assisted distal gastrectomy (LADG) by objective evaluation. Methods A total 167 pT1N0M0 gastric cancer patients underwent LAPPG( n = 70) and LADG( n = 97) were retrospectively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 29 publications
0
31
1
Order By: Relevance
“…Moreover, comparing with patients with an antral cuff of 1.5 cm, better postoperative outcomes were found in those who had a 2.5 cm antral cuff [40]. In addition, the incidence of gastric stasis was lower with preservation of infra-pyloric blood supply in conventional pylorus-preserving gastrectomy (cPPG), which ranged from 5.7 to 8.0% reported previously [7,9,41,42]. Kiyokawa et al showed that delayed gastric emptying was found in 8.5% patients from the cPPG group but no patient in group with the preservation of infra-pyloric vein [42].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Moreover, comparing with patients with an antral cuff of 1.5 cm, better postoperative outcomes were found in those who had a 2.5 cm antral cuff [40]. In addition, the incidence of gastric stasis was lower with preservation of infra-pyloric blood supply in conventional pylorus-preserving gastrectomy (cPPG), which ranged from 5.7 to 8.0% reported previously [7,9,41,42]. Kiyokawa et al showed that delayed gastric emptying was found in 8.5% patients from the cPPG group but no patient in group with the preservation of infra-pyloric vein [42].…”
Section: Discussionmentioning
confidence: 83%
“…The first meta-analysis, which was published in 2014 [10], demonstrated that PPG had superior benefits in terms of lower incidence rates of early dumping syndrome, gastritis, and bile reflux as well as regaining of weight. According to the Japanese Gastric Cancer Treatment Guidelines and considerable newly published studies with relatively comprehensive data [5,7,11,12], indications as well as standardized management and treatment for PPG have been well established. Therefore, we performed an updated meta-analysis to demonstrate the surgery efficacy, oncologic safety, and function recovery of PPG.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to just one articles with < 3cm antral cuff was published, the results may be influenced by the relatively small sample size. Additionally, the incidence of gastric stasis was lower with preservation of infra-pyloric blood supply in conventional pylorus-preserving gastrectomy (cPPG), which ranged from 5.7% to 8.0% reported previously[7,9,39,40]. Kiyokawa et al showed that no DGE patient was found with the preservation of infra-pyloric vein, while 8.5% patients from the cPPG group[40].…”
mentioning
confidence: 94%
“…Moreover, the retainment of pyloric cuff and vagal nerve in PPG provided advantages such as ameliorating postoperative gastritis, bile reflux, early dumping syndromes and improving nutritional status [4,5]. In PPG, the infrapyloric LNs are routinely dissected with preserving the infra-pyloric vessels, and the supra-pyloric LNs are usually omitted to preserve the right gastric artery and the hepatic branch of the vagal nerve [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation